2010
DOI: 10.1007/s10067-010-1436-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against oxidized low-density lipoprotein are associated with subclinical atherosclerosis in recent-onset rheumatoid arthritis

Abstract: there is increased prevalence of carotid plaques in patients with recent-onset RA compared to matched controls. The accelerated atherosclerosis is predicted by age, CRP, and oxLDL-ab. The association of plaques with elevated CRP and OxLDL-ab support the hypothesis that chronic systemic autoimmune inflammatory process is probably a driving force for premature atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
0
20
2
1
Order By: Relevance
“…A younger RA group might also be responsible for the lower mean IMT than in other reports [25]. Although Ahmed et al analyzed an equally young group of RA patients, severe atherosclerosis was more frequent in their cohort [27]. This might be due to the fact that in 12.5% of the RA patients assessed by Ahmed et al were diabetic, as opposed to none in the present study; and in 22.5% of the RA patients in those authors' study reported a significant family history of CV diseases, while patients with a significant family history of CVD were excluded from the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…A younger RA group might also be responsible for the lower mean IMT than in other reports [25]. Although Ahmed et al analyzed an equally young group of RA patients, severe atherosclerosis was more frequent in their cohort [27]. This might be due to the fact that in 12.5% of the RA patients assessed by Ahmed et al were diabetic, as opposed to none in the present study; and in 22.5% of the RA patients in those authors' study reported a significant family history of CV diseases, while patients with a significant family history of CVD were excluded from the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…Two studies showed that plaques were more prevalent in early RA cohorts than among healthy controls,30 32 whereas one study found the prevalence to be similar among early RA cases and controls 31. As an aggregate, it seems that enhanced atherogenesis occurs soon after RA symptom onset (figure 1) and that this is subsequently ongoing.…”
Section: Subclinical CV Changesmentioning
confidence: 99%
“…In early RA, antibodies against oxidised LDL30 and anti-modified citrullinated vimentin levels67 have been demonstrated to correlate positively with subclinical atherosclerosis. However, in the 5-year prospective study already mentioned, the incidence of overt CV events did not correlate with immunological mediators such as RF, anti-citrullinated peptide antibody and antinuclear antibodies during the first years of RA 48…”
Section: Risk Factorsmentioning
confidence: 99%
“…Anticyclic citrullinated peptide antibodies (anti-CCP), IgM rheumatoid factor, circulating immune complexes, proinflammatory cytokines including TNF α and IL-6, Th0/Th1 cells, decreased folate and vitamin B12 productions, and impaired paraoxonase activity, among others, may all be further involved in the development of vascular disease in RA [8587]. Epigenetic data indicate that defective DNA methylation might also be relevant to CVD and AT development in RA, so that it has been shown hypomethylation of IL-6 promoter [35].…”
Section: Epigenetic Alterations Inflammation and Cardiovascular mentioning
confidence: 99%